2020
DOI: 10.1038/s41598-020-65312-6
|View full text |Cite
|
Sign up to set email alerts
|

External Airborne-agent Exposure Increase Risk of Digestive Tract Cancer

Abstract: previous studies have suggested that in addition to respiratory system cancers, exposure to external airborne agents (EAAs) may also affect the risk of digestive tract cancer. However, previous epidemiological studies have been limited. To clarify this relationship, we conducted a Workers' Korea National Health Insurance Service cohort study. The EAA exposure group comprised participants who had ever visited a hospital as an inpatient for 'lung diseases due to external agents'. The reference population compris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 39 publications
1
6
0
Order By: Relevance
“…We defined severe external airborne agents' exposure group as patients with ICD-10 codes from J60 to J70, except J69, from the NHIS-HealS in the follow-up periods. It indicated a severe respiratory abnormal outcome closely related to exposure to external airborne agents as seen in previous study [26].…”
Section: Exposure To Severe External Airborne Agentssupporting
confidence: 76%
“…We defined severe external airborne agents' exposure group as patients with ICD-10 codes from J60 to J70, except J69, from the NHIS-HealS in the follow-up periods. It indicated a severe respiratory abnormal outcome closely related to exposure to external airborne agents as seen in previous study [26].…”
Section: Exposure To Severe External Airborne Agentssupporting
confidence: 76%
“…External airborne agents (EAA), such as mineral dust, vapor, and engine exhaust, are substances that are released into the atmosphere and exposed to workers [ 18 ]. Miners and quarriers are exposed to EAA in their working environments [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…EAA is known to cause lung cancer and various respiratory system diseases, including pneumoconiosis [ 24 , 25 ]. Several studies have demonstrated that workers exposed to EAA have an increased risk of esophageal cancer, stomach cancer, and all GI cancers [ 18 , 26 , 27 , 28 , 29 , 30 ]. A previous study postulated that the lung clearance system can release inhaled EAA into the oral cavity, where they are constantly swallowed and enter the digestive tract [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are no direct studies to date assessing the contribution of ingested particles from wildfire smoke. However, gastrointestinal exposures via the mucociliary escalator can occur (W. Lee et al, 2020). Additional occupational-related exposures are possible through the ingestion route.…”
Section: Ingestion Exposure Routementioning
confidence: 99%